The prevalence of and resistance to antimicrobial agents of Bacillus cereus isolates from foodstuffs - J. Schlegelova; J. Brychta; E. Klimova; E. Napravnikova; V. Babak (Veterinární Medicína, 2003)
The study was aimed at the assessment whether foodstuffs contaminated with Bacillus cereus (B. cereus) may concurrently be vectors of spreading resistance. The contamination of foodstuffs with B. cereus strains was found in 31% of dairy and in 28% of meat products tested. Only one product from skimmed milk was contaminated. High-fat milk products that were heat-treated during the technological process (87 samples), as well as heat-treated meat products (65 samples), were contaminated significantly frequently (63% and 48% of the samples respectively) (P < 0.01). Almost all B. cereus isolates displayed low susceptibility to ampicillin, cephalothin, and to oxacillin. Except for streptomycin (STR) resistance, resistance to other 8 antimicrobial agents occurred sporadically. The STR resistant isolates came particularly from spreading buffer (8 samples) (P < 0.05). It was established that the same samples were contaminated with two subpopulations of B. cereus with different STR resistances. The frequent occurrence of B. cereus in foodstuffs with either fat content and/or subject to heat treatment in processing makes these products risky, however, our study did not confirm that foodstuffs contaminated with B. cereus are concurrently vectors of transmissible resistance genes.